A transformations framework for mainstreaming a nature-based solutions approach - Esther Carmen; Alhassan Ibrahim; Kirsty Blackstock; Kerry Waylen (Nature-Based Solutions)
As the integrity and extent of many natural ecosystems continues to decline, the concept of Nature-based Solutions (NbS) is gaining traction as a means to reverse such trends. However, uptake of an NbS approach across society is often piecemeal or partial. This paper argues that a deeper connection with the literature on transformations will help realise the full potential of NbS for enabling sustainable futures. Whilst others have already noted the concept of transformations to be relevant to NbS, many insights from the sustainability transformations literature remain underutilised by those working with NbS.In this paper, we provide a conceptual framework to enable more ambitious and widespread uptake of NbS. We do this by identifying and drawing on key conceptual perspectives and frameworks from the sustainability transformations literature. This framework identifies key components (current system, future visions, process and an iterative approach) to consider when planning strategic actions. The framework strengthens the links between transformations and NbS concepts for a variety of stakeholders: as well as guiding NbS practitioners, it can also support action-orientated research to help steer NbS to achieve transformational change.